Means and Ways of Translating Foreign Collocations: Linguistic and Contextual Approaches - Ashrapova Nargiza Muxitdinovna (Peerian Journals Publishing, 2025)
This study investigates the effective means and ways of translating foreign collocations from English into Uzbek, emphasizing the influence of idiomaticity, semantic transparency, and collocational strength on strategy choice. Using a bilingual corpus compiled from news, academic, and technical texts, collocations were classified as lexical or grammatical, transparent or opaque, and culture-bound or neutral. Strategies such as literal translation, calque, transposition, modulation, equivalence, explicitation, and phraseological substitution were tested. Evaluation was based on expert judgment and an error typology including selectional clash, register drift, and cultural mismatch. Results indicate that context-sensitive strategies outperform literal or calque methods for opaque and culture-bound units, whereas transparent collocations allow faithful, form-preserving translation. The paper proposes a decision framework linking collocation type and discourse function to translation strategy, offering practical implications for translators, educators, and CAT-tool developers
Keywords: collocations; translation strategies; equivalence; explicitation